MENINGKATKAN KEMAMPUAN SISWA DALAM MELENGKAPI CERITA RUMPANG MELALUI METODE INKUIRI DI KELAS IV SDN N0. 90 KOTA UTARA KOTA GORONTALO - Sumarni Mohamad (Jurnal Inovasi, 2011)
The problem in this research is "whether the inquiry method fourth grade students' ability SDN No. 90 North City hiatus complete story will be increased". The hypothesis of action in this study is "if the inquiry method applied to the ability of fourth grade students of SDN No. 90 North City hiatus complete story will be increased". The results on the first cycle of material offerings complement the story hiatus with the inquiry method taught by 2 x 35 minute data showed that 17 students or 63.52% were independent in completing the task. This indicates that still there are 11 students who must be guided in doing the tasks given. student learning outcomes in this cycle show that 15 people (53%) obtained a value of 65% and above, with an average absorption of 61.30%. These results are still far from the criteria applied in this research that is at least 65. Failure to achieve this cycle of learning is more influenced by ineffective learning ctivities. Deficiency in this cycle further enhanced on the second cycle, namely the presentation of the material complements the story hiatus with the inquiry method. The results obtained on the second cycle is 26 students or 92.9% students had been independent in a given task. This learning independence have an impact on student acquisition. Of the 28 students who were given the action, 26 students or 92.2% obtained a value of 65 and over. With the acquisition of students above, it can be concluded that through the inquiry method of learning the story complete hiatus, the ability of students can be improved.